Analysis of Funny Metaphor Used in Instagram’s Captions - Muhammad Fitriyanto; Ismara Vernanda; Vita Lutfiah; Yudhistira Taufiqi Mulyana; Husnul Athiya (Universitas Brawijaya, 2020)
This paper aims to examine the metaphors used in